Maternal Psychological Distress and Executive Functions Are Associated During Early Parenthood – A FinnBrain Birth Cohort Study - Nordenswan, Elisabeth; Deater-Deckard, Kirby; Kataja, Eeva-Leena; Karrasch, Mira; Pelto, Juho; Laine, Matti; Karlsson, Hasse; Karlsson, Linnea; Korja, Riikka (Frontiers in Psychology, 2021)
Parental executive functioning (EF) and parenting behaviors can be affected by the multiple stressors that are often present during early parenthood. However, little is known about how commonly experienced psychological distress during early parenthood is associated with parental EF capacity. We explored the links between psychological distress and EFs in a general population sample of 150 Finnish birth cohort mothers with 2.5-year-old children. The symptoms of depression, anxiety, insomnia, and poor couple relationship adjustment were measured with the self-report questionnaires EPDS, SCL-90, AIS and RDAS. EFs were assessed with five computerized Cogstate tasks. When the psychological distress measures were added to a hierarchical regression analysis as continuous variables, no significant single or additive associations with EFs were found. When the distress measures were dichotomized to compare symptoms below/above cutoffs indicating clinically elevated levels, single distress domains remained as non-significant predictors, but a cumulative risk index of the number of concurrent clinically elevated distress domains was significantly associated with EFs. Thus, mothers with a higher number of concurrent clinically elevated psychological distress domains (i.e., depression, anxiety, insomnia, and poor couple relationship adjustment) tended to have lower EFs. This association is possibly bi-directional – clinically elevated distress within several domains could have a cumulative, depleting effect on maternal EF capacity, but a lower EF capacity could also increase the vulnerability for experienced distress within several concurrent domains. Longitudinal studies are needed to clarify potential causal links between stressors and EF.